The development of E-LKPD through problem-based learning to improve the sixth-grade students’ Mathematics mastery - Nyoman Ari Negari; Lilik Sabdaningtyas; Nurhanurawati Nurhanurawati (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
The purpose of this research was to create a Mathematic LKPD based on Problem Based Learning for the subject of integer arithmetic operations in elementary school. The desire for learning that may improve students' abilities to solve problems, think critically, and inspire curiosity drove the development of this Mathematics LKPD. This was a research and development project (R&D), with data collection and basic research, planning, product development, limited testing, and final product revision being the primary steps. The participants in this study were sixth-grade teachers of SD Negeri 1 Rama Murti located in Seputih Raman district, Central Lampung, Indonesia, with a purposive sampling technique. The research sample consisted of 32 sixth-grade students of the school. Observation and questionnaires were employed to obtain data using a qualitative descriptive analysis. The development of the PBL-based LKPD materials in primary schools was extremely viable to use in learning, according to the findings of the research and debate. This corresponds to the findings of the material experts' validation, the results of the design experts' validation, the results of the media experts' validation, and the findings of the teacher testing.